The Impact of COVID-19 Pandemic on the Global Economy and Environment - ZHILENKO, Vilena Yurievna; AMIROVA, Elmira Faylovna; LOMAKIN, Denis Evgenevich; SMOKTAL, Nikolai Nikolaevich; KHAMKHOEVA, Fatima Yakhievna (Journal of Environmental Management and Tourism, 2021)
As a result of the appearance of a new coronavirus infection in the world in 2019 (COVID-19), there was a change in all spheres of people's lives. The measures taken to reduce the spread of the virus have had a negative impact on the economy and a positive impact on the environment. This research is aimed at studying the positive impact of COVID-19 on the environment and studying the global economic recession in connection with the quarantine measures that were accepted. The research used an analytical approach based on the analysis of global statistics and available scientific literature on COVID-19. The main macroeconomic indicators are analyzed, and the state of the atmosphere and hydrosphere during the isolation period is assessed. As a result of the research, the main measures that contribute to the elimination of the economic downturn are identified, as well as the main ways to achieve long-term environmental benefits. Thus, the implementation of the proposed strategies in ecology and economics can be useful for global economic and environmental sustainability.